COVID-19: An Experience from a Tertiary Care Hospital of Nowshera: COVID-19 - Hamzullah Khan , Mohammad Zahid Khan , Mian Muhammad Naveed (Journal of Rawalpindi Medical College, 2020)
Objective: To determine the frequency of COVID-19 and characteristics of patients presenting to the COVID-19 clinic at Qazi Hussain Ahmed Medical Complex (QHAMC) Nowshera. Methodology: This cross-sectional study was conducted from 21st Feb 2019 to April 8, 2020, in QHAMC Nowshera. Relevant information was collected on a pre-designed Performa prepared following the objectives of the study. Results: Out of 220 patients, 165(75%) were males, and 55(25%) females. 96(43.6%) of the patients were in the age range 18-30 years followed by 52(23.6%) in age range 31-45years and 17(7.7%) with age>60 years etc. Out of total the nasopharyngeal swabs of 26(11.6%) strong suspects were sent for PCR testing. 208(94.5%) were sent home while 12(5.5%) were advised quarantine. Forty-seven (21.4%) had a travel history to an epidemic area in the last 14 days. 51(23.2%) had a positive history of contact. Eighty-five (38.6%) had a fever and sore throat followed by 27(12.3%) with (fever & cough), 24(10.9%) with (cough and shortness of breath/dyspnea) and 14(6.4%) with a simple flue, etc. Out of 26 cases, 6(2.7%) were COVID-19 Positive, 12(5.5%) were negative and results of 8(3.6%) were still awaited. The PCR repeated the test for confirmed cases showed; 4(1.8%) negative, one died and one was refractory positive. A positive correlation (p=0.03, r=0.4) of an increase in age with the severity of the disease/outcome was recorded. Conclusion: The frequency of infectivity with COVID-19 was 2.6%. A higher number of patients with mild symptoms attend the COVID clinic. The rate of infection and mortality was higher in age> 60 years.